National and regional description of healthcare measures among adult Medicaid beneficiaries with schizophrenia within the United States. (31st December 2022) - Patel, Charmi; Pilon, Dominic; Gupta, Deepshekhar; Morrison, Laura; Lafeuille, Marie-Hélène; Lefebvre, Patrick; Benson, Carmela
Abstract: Aims: Provide the first national description across the US of variations in healthcare measures in 2018 among Medicaid beneficiaries with schizophrenia. Materials and methods: Adult beneficiaries with ≥2 diagnoses for schizophrenia, and continuous enrollment with consistent geographical data in all of 2018 were identified from Transformed Medicaid Statistical Information System (T-MSIS) Analytic Files (TAF) data for 45 of 50 states. Antipsychotic (AP) utilization rates, including long-acting injectable APs (LAIs), quality metrics, and all-cause healthcare resource utilization and costs for claims submitted to Medicaid were reported nationally and by state. Pearson correlation evaluated associations between LAI utilization and total healthcare costs at state and county levels. Results: Across the US 688, 437 patients with schizophrenia were identified. The AP utilization rate was 51% (state range: 24–77%), while the LAI utilization rate was 13% (range: 4–26%). The proportion of patients adherent to any AP was 56% (range: 19–73%). Within 30 days post-discharge from an inpatient admission, 22% (range: 8–58%) of patients had an outpatient visit, and 12% (range: 4–48%) had a readmission. The proportion of patients with ≥1 inpatient admission and ≥1 emergency room visit was 34% (range: 19–82%) and 45% (range: 20–70%). Per-patient-per-year total healthcare costs averaged 32, 920 (range: 717–93, 972). At the county level, a weak negative correlation was observed between LAI utilization and total healthcare costs. Limitations: This study included Medicaid beneficiaries enrolled with pharmacy and medical benefits, including beneficiaries dually eligible for Medicare; results cannot be generalized to the overall schizophrenia population or those with other payer coverage. Conclusions: In 2018, half of beneficiaries with schizophrenia did not submit any claims for APs to Medicaid, nearly half had an emergency room visit, and one-third had an inpatient admission. Moreover, healthcare measures varied considerably across states. These findings may indicate unmet treatment needs for Medicaid beneficiaries with schizophrenia. PLAIN LANGUAGE SUMMARY: Schizophrenia is a severe mental disorder that poses a large health, social, and cost burden to patients and society. While treatment with antipsychotic medications can reduce the number of relapses and hospitalizations, many patients do not adhere to treatment, which can lead to poor symptom control and further use of healthcare services. Interestingly, these measures of schizophrenia care seem to vary across US states. Therefore, we ran the first study to describe the regional differences in antipsychotic use, measures of quality of care, healthcare use, and healthcare costs among Medicaid-insured patients across the US in 2018. Our results showed that only half of patients used antipsychotics in 2018 (with a range of 24–77% across states) and the proportion of patients adherent to antipsychotic treatment was low (range of 19–73%). Additionally, nearly half of all patients had an emergency room visit (range of 20–70%), and one-third had an inpatient admission (range of 19–82%). These findings highlight large variations in antipsychotic use, performance measures, and healthcare use, possibly due to regional differences in unmet needs in schizophrenia care for Medicaid-insured patients in the US. Since use of inpatient and emergency room services was consistently high in specific states or regions, and yearly healthcare costs per patient varied from 717–93, 972 (mean = 32, 920), there may be a particularly high burden in certain areas of the country where patients with schizophrenia may potentially be experiencing multiple relapses. Further research is needed to identify policies that may help narrow these regional differences.